Critical discussion on ancient language evolution tool to discover world history - Bawazir, ola; Zakarya, Heba; Yaacob, Solehah@Nik Najah Fadilah; , (International Islamic University Malaysia, 2017)
GOMBAK, 8 November 2017 – The critical discussion on ancient language evolution might be considered as a tool to expand the concept of language thinking ability, Assoc. Prof. Dr. Solehah Yaacob of the Department of Arabic Language and Literature, told listeners of IIUM.fm recently.